Nuts, hexagonal, slotted (castellated), reduced height, reduced across flats, with MJ threads, classifications. 450 MPa (at ambient temperature)/425°C, 600 MPa (at ambient temperature)/235°C, 600 MPa (at ambient temperature)/315°C, 600 MPa (at ambient temperature)/650°C, 900 MPa (at ambient temperature)/235°C, 900 MPa (at ambient temperature)/730°C and 1100 MPa (at ambient temperature)/600°C. Dimensions. (15th November 1997) - British Standards Institution,
No abstract available